PENGARUH PROFITABIITAS, LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Marhendra, Farkhan; Sunarto, Sunarto (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study is conducted to evaluate the extent to which profitability, liquidity, and capital structure can affect the value of a company. In this study, profitability is measured through Return on Assets (ROA), liquidity using current ratio, while capital structure is seen from the ratio of debt to equity (DER). Firm value itself is represented by the Price to Book Value (PBV) ratio. The data used is sourced from the company's published financial statements and analyzed using quantitative methods. A purposive sampling technique was used to determine the sample, while multiple linear regression tests were applied in the analysis process. The findings show that profitability has a significant positive impact on firm value. Meanwhile, liquidity shows no significant effect, and capital structure has a significant negative effect on firm value. These findings are expected to provide strategic considerations for company management in making financial decisions so that the company value remains competitive in the eyes of investors.